2011
DOI: 10.1111/j.1476-5381.2010.01162.x
|View full text |Cite
|
Sign up to set email alerts
|

The novel phospho‐non‐steroidal anti‐inflammatory drugs, OXT‐328, MDC‐22 and MDC‐917, inhibit adjuvant‐induced arthritis in rats

Abstract: BACKGROUND AND PURPOSEThe use of non-steroidal anti-inflammatory drugs (NSAIDs) in the treatment of rheumatoid arthritis (RA) is limited by their toxicity. We evaluated the anti-inflammatory efficacy and safety of three novel modified NSAIDs, phospho-aspirin, phospho-ibuprofen and phospho-sulindac. EXPERIMENTAL APPROACHWe determined the anti-inflammatory effects and gastrointestinal safety of the phospho-NSAIDs in the rat adjuvant arthritis model and studied their mechanism of action in cultured cells, Cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 36 publications
6
60
0
Order By: Relevance
“…The jpet.aspetjournals.org differences in efficacy between the two were statistically not significant; such lack of significance is probably caused by a lack of power. Nonetheless, we deem these differences as clinically relevant, especially when the greater safety of PI is factored in (current data and Huang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The jpet.aspetjournals.org differences in efficacy between the two were statistically not significant; such lack of significance is probably caused by a lack of power. Nonetheless, we deem these differences as clinically relevant, especially when the greater safety of PI is factored in (current data and Huang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…1, inset). PI has strong antiinflammatory properties both in vitro and in animal models of arthritis, and it was shown to have far better gastrointestinal safety than conventional ibuprofen (Huang et al, 2011). PI inhibited cancer cell growth 16 to 23 times more potently than its parent drug, ibuprofen.…”
Section: Introductionmentioning
confidence: 99%
“…PFTS was generated by modifying the carboxylic group of FTS to enhance its efficacy, as we have done with other anticancer agents [20][21][22]26,32,33]. PFTS has a higher capacity to inhibit Ras activity and is more effective than FTS in suppressing pancreatic cancer cell growth.…”
Section: Discussionmentioning
confidence: 98%
“…Goldberg et al have shown that modifications of the FTS carboxylic group by esterification or amidation yield compounds with improved growth inhibitory activity compared to FTS [19]. We have also demonstrated that covalent modifications of several carboxylic nonsteroidal antiinflammatory drugs generate compounds of superior efficacy and safety [20][21][22]. With this in mind, we synthesized the novel phospho-FTS (PFTS; MDC-1016), following the formula FTS-butane-diethyl phosphate ( Figure 1A).…”
Section: Introductionmentioning
confidence: 92%
“…The modification of pharmacologically active compounds may lead to a new finding of novel drugs with diverse pharmacological activities [8]. Chemical modification of aspirin, for instance, has been reported to reduce gastrointestinal toxicity and exhibited diverse biological activities such as anticancer [9], antiinflammatory [10], and antibacterial [11,12] activities. Aspirin 2 Journal of Chemistry bearing active functional groups such as diethyl phosphate and nitro groups has been reported to have anticancer activity against pancreatic and colon cancers [13,14].…”
Section: Introductionmentioning
confidence: 99%